Reigniting labour productivity growth in developing countries: Do structural reforms matter? - Kwamivi Gomado (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
While the negative effects of the 2008 global financial crisis on labour productivity are still fresh in people's minds, the COVID-19 pandemic raises concerns that productivity will continue to decline. To boost labour productivity and regain economic performance, there is an empirical consensus on the role of structural reforms that allows an efficient reallocation of resources such as labour by reducing rigidities in markets. This study analyses the role of certain structural reforms in improving labour productivity in 35 developing countries over the period of 1990-2014. From the local projection method, our results show that structural reforms have a positive impact on productivity growth in the short and medium terms. The results also illustrate that reforms induce an efficient reallocation of resources within but not between sectors. Taking the business cycle into account in estimates shows that structural reforms stimulate labour productivity growth better in periods of low economic growth.
Keywords: D24; O16; O24; O43; 330; labour productivity; structural reform; local projection method; business